2017
DOI: 10.4037/ccn2017999
|View full text |Cite
|
Sign up to set email alerts
|

Access to Continuing Education for Critical Care Nurses in Rural or Remote Settings

Abstract: Caring for the critically ill does not occur solely in large medical centers or urban areas. Nurses practicing in rural or remote settings practice as nurse generalists, caring for a wide range of patients, including those needing critical care. As a nurse generalist, the need for a wide variety of skill sets challenges nurses in rural areas to maintain current practice through continuing education across many content areas. They also may not come in contact with critically ill patients or emergent situations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Continuous education is vital as it ensures that professionals can adequately monitor their own professional development to provide safe and efficient services (Directive 2005/36/EC and EFN Strategic & Operational lobby plan 2014-2020, revised 2016; National league for Nursing, 2019). Other researchers have suggested that continuous education is crucial to maintaining the skills and competences that are needed to operate in a practical environment (Hendrickx and Winters, 2017) and that it significantly impacts the attendee's knowledge, skills, attitudes and behaviors (Harden et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous education is vital as it ensures that professionals can adequately monitor their own professional development to provide safe and efficient services (Directive 2005/36/EC and EFN Strategic & Operational lobby plan 2014-2020, revised 2016; National league for Nursing, 2019). Other researchers have suggested that continuous education is crucial to maintaining the skills and competences that are needed to operate in a practical environment (Hendrickx and Winters, 2017) and that it significantly impacts the attendee's knowledge, skills, attitudes and behaviors (Harden et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional continuing learning methods that usually use face-to-face classes as the major approach can be difficult for nurses to attend. Heavy workloads, time or energy constraints, geographic distance, learning costs, and lack of learning opportunities or support from supervisors were the key barriers to nurses’ participation in continuing education programs [ 11 , 12 ], especially for those working in rural and remote healthcare settings [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although taking part in web conferences generally requires little more than Internet access in terms of technology, it is also essential for participation that users have adequate time, adequate workspace, and a reliable Internet connection. Communication technology can reduce the professional and social isolation of rural nurses [31], address the challenges of travel to access urban-based in-person education [53], and support skill development through online learning [25], but these tools must first be accessible to nurses in their workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that rural nurses have the capacity to provide safe and effective care, and to maintain competence, it is important that they have opportunities to update their clinical knowledge and skills through continuing education programs [25]. Rural nurses require education that is relevant to their practice and patient population [19, 25]. Relevant continuing education has been shown to increase self-reported confidence, competence, and job satisfaction among rural nurses and to expand their range of practice [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation